A community-based study for assessment of growth and development of low-birth-weight infants, in Sanwer Tehsil of Indore, Madhya Pradesh - Sharma, Neelima; Wavare, R. R.; Gautam, Pooja; Sharma, Preksha; Sharma, Neha (International Journal Of Community Medicine And Public Health, 2021)
Background: The objective of study was to assess the growth and development of low-birth-weight (LBW) infants. Methods: The study was conducted in community health center of Sanwer Tehsil (Indore District) in the state of Madhya Pradesh under the department of community medicine of Sri Aurobindo medical college and PG institute, Indore. A total of 150 babies were registered and followed up for study. Results: Male preponderance was observed in our study with 70 males and 66 females. Out of total 80 LBW neonates (44 males and 36 females), 6 were home deliveries, while similar equal distribution among primipara and bipara (34 and 30 respectively) was noted. It was found that maximum number of LBW infants (11.76%) were found in the mothers age group of 21 and 25. Conclusions: c2 value suggested that parity was not significantly correlated to LBW but multiparas with >3 deliveries were more prone to deliver a low-birth-weight baby. National programmes targeting to address low birth weight are the need of the hour.